Colonial signature of the alarm pheromone and chemical differences between hornet workers - Mélissa Haouzi; Florian Bastin; Elfie Perdereau; Chloé Humbert; Bastien Play; Laureen Beaugeard; Eric Darrouzet (PLoS ONE, 2026)
The social organisation of eusocial insects is based on an effective communication system in which pheromones play a central role. Among these chemical compounds, the alarm pheromone is an essential component of colonial survival by inducing nestmates recruitment and defensive behaviours. In this study, we investigated the alarm pheromone composition produced in the venom gland of workers of the invasive Yellow-legged hornet Vespa velutina nigrithorax , focusing on two aspects: first, variations between different colonies, and second, differences related to the activities of workers in the colony at a given time. Here, we examined four specific activities: animal foragers, builders, defenders and material foragers. Our results reveal significant chemical heterogeneity in the alarm pheromone among workers, highlighting a strong colony-specific chemical signature as well as a variability linked to workers’ activities. Notably, animal foragers and builders exhibited distinct pheromone profiles with discriminant chemical compounds. This study therefore suggests that the alarm pheromone could be used as a recognition signal in Vespidae species, both at the inter and intra-colonial levels. Such findings provide valuable insights into the chemical ecology of invasive species and open new perspectives on the role of pheromones in colony coordination and defense mechanisms.